Defenders and critics of Franciscan life: essays in honor of John V. Fleming - Cusato, Michael F.; Geltner, Guy; Fleming, John V. (The medieval Franciscans, 2009)
Editors' introduction -- Preface: A literary apostolate : John Fleming and the Franciscan literature of the middle ages / D. Vance Smith -- Part I: Franciscan exegesis -- Francis of Assisi, deacon : an examination of the claims of the earliest Franciscan sources, 1229-1235 / Michael F. Cusato -- Tobit's dog and the dangers of literalism : William Woodford, O.F.M., as critic of Wycliff's exegesis / Alastair Minnis -- Part II: Students and scholars -- Franciscan learning : university education and biblical exegesis / William J. Courtenay -- Using, not owning duties, not rights : the consequences of some Franciscan perspectives on politics / Janet Coleman -- Langland and the Franciscans on dominium / Lawrence M. Clopper -- William of St. Amour's De periculis novissimorum temporum : a false start to medieval anit-fraternalism? / G. Geltner -- Part III: Franciscan critics and critics of theGranciscans -- History as prophecy : Angelo Clareno's chronicle as a spiritual Franciscan apocalypse / David Burr -- Views of John XXII as a heretical pope / Patrick Nold -- Kicking the habit : the campaign against the friars in a fourteenth-century encyclopedia / Penn Szittya -- Si Sind all Glichsner : anti-fraternalism in Medieval and Renaissance German literature / Geoffrey Dipple -- Part IV: Franciscan legacies -- Imitatio francisci : the influence of Francis of Assisi on late medieval religious life / Lester K. Little -- Louis IX : preaching to Franciscan and Dominican brothers and nuns / William Chester Jordan -- Preaching as playwriting : a semi-dramatic sermon of the fifteenth century / Katherine l. Jansen